2019
DOI: 10.29328/journal.cjog.1001028
|View full text |Cite
|
Sign up to set email alerts
|

The validity of progesterone level on hCG injection day in the prediction of IVF/ICSI cycles’ outcome

Abstract: The validity of progesterone level on hCG injection day in the prediction of IVF/ICSI cycles' outcome. Clin J Obstet Gynaecol. 2019; 2: 095-100.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Another study reported that pregnancy rate in the followed-up cases was 36.7%. A significant negative association was detected between progesterone level at hCG day and the pregnancy outcomes, as serum progesterone has significantly high in non-pregnant compared to pregnant cases (2.26 vs 1.84, p = 0.018) [14] .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Another study reported that pregnancy rate in the followed-up cases was 36.7%. A significant negative association was detected between progesterone level at hCG day and the pregnancy outcomes, as serum progesterone has significantly high in non-pregnant compared to pregnant cases (2.26 vs 1.84, p = 0.018) [14] .…”
Section: Discussionmentioning
confidence: 91%
“…Another study handling the same perspective included a total of 302 cases. Patients were started on antagonist (n=241), short (n=47) or long (n=14) agonist protocols, according to their infertility evaluation [14] . Comparable to the present work, one study included a total of 12 cases and patients were divided according to progesterone level into two equal groups; one with progesterone levels <1.5ng/ml, while the other group had higher levels [15] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations